Cross-cultural academic mentoring dyads: a case study. Issue 2 (15th March 2019) - Daniel, Amber; Franco, Suzanne; Schroeder, Noah L.; Cenkci, Ada T.
ABSTRACT: Mentoring and diversity are disparate elements of interest within universities. We used a descriptive case study to provide an understanding of the interaction between diversity and the academic mentoring process. The conceptual framework is two-fold: (a) that mentoring relationships progressed through four phases: Initiation, Cultivation, Separation and Redefinition; and (b) that mentors play four roles: Advisor, Instructor, Employer, and Agent of Socialization. Interviews with a cross-cultural mentoring dyad consisting of a graduate student and her mentor revealed that the dyad had experienced the first two of the mentoring phases (Initiation and Cultivation) in their entirety, with elements of the second two phases (Separation and Redefinition) becoming apparent; and that the mentor had fulfilled all of the faculty roles. We identified how the four phases of mentoring relationships and the four faculty roles adopted within such relationships work in tandem across three broad stages of relational development.